Masalah yang Dialami Perawat Dalam Menangani Remaja Penyalahguna NAPZA: A Systematic Review - Dwi Suratmini; Novy Helena Catharina Daulima (FORIKES, 2020)
Nurse’s efforts in adolescent as the most drug-abusing population have not been able to run optimally as indicated by the increase in prevalence and relapse rates, so further studies are needed regarding the problems experienced by nurses during the handling process. The aim of this systematic review was to find out the problems experienced by nurses while dealing in adolescent drug users. The database were used EBSCOhost, ProQuest, Sage Publication, and Springerlink identified and published from 2016-2020, in English, and in the nurse population both in hospitals or other rehabilitation. The keywords were